Attitude of Coastal Rural Youth towards Some Selected Modern Agricultural Technologies - Uddin, ME; Rashid, MU; Akanda, MGR (Journal of Agriculture & Rural Development, 2008)
The main objective of the study was to determine the attitude of the coastal rural youth towards some selected modern agricultural technologies. Data were collected from randomly selected 91 coastal rural youth of Patuakhali district using a pre-tested structured interview schedule during 15 May to 31 May 2007. Attitude of the coastal rural youth towards some selected modern agricultural technologies was the dependent variable of the study. Ten selected individual characteristics of the coastal rural youth namely age, education, family size, family farm size, family annual income, aspiration, innovativeness, extension media contact, agricultural knowledge and time spent in agricultural activities were considered as the independent variables of the study. Highest proportion (71.43%) of the coastal rural youth had moderately favorable attitude while 10.99% and 17.58% youth showed unfavorable and favorable attitude, respectively, towards selected modern agricultural technologies. Education, innovativeness and agricultural knowledge of the coastal rural youth had positive and significant relationship with their attitude towards selected modern agricultural technologies. The other variables did not show any significant relationship. DOI: http://dx.doi.org/10.3329/jard.v6i1.1670 J Agric Rural Dev 6(1&2), 133-138, June 2008